Inappropriate left ventricular mass in a young population - Escudero, Eduardo M. (2012)
The concept of inappropriate left ventricular mass (iLVM) was introduced to distinguish between compensatory increases in LVM and clinically relevant, maladaptive changes.2 iLVM is that which exceeds the expected value for a given individual based on sex, body size, and stroke work, and it is associated with an increased cardiovascular risko abstract available.